Customer Satisfication Pada Pembelian Smartphone Samsung Dilihat Dari Trust In Brand, Brand Image Dan Word Of Mouth Di Sarana Smartphone Kota Solok - Febsri Susanti; Doni Marlius; Suci Kahirumi (JURNAL PUNDI, 2021)
This competition appears along with the development of increasingly sophisticated technology, encouraging various types of changes system in the world for example in the business world changes system such as system in trading, marketing, how to make transaction, and delivery of information still changing. The purpose of this study is to examine the effect of the trust in brand, brand image dan word of mouth terhadap customer satisfication purchases samsung smartphone in Sarana Smartphone Solok City. This research is a quantitative method, using the technique of multiple linear regression. The sample in this study amounted to 65 customers. Techniques used in collecting data is the spread of questionnaires, interviews and observation. This study uses SPSS  Version 16 to calculate and analyze data. The results showed that the partially trust in brand, brand image had a positive and significant effect, while word of mouth had not significant effect on customer satisfaction purchases samsung smartphone in Sarana Smartphone Solok City.